Synergy and Mechanism of the Action of the Combination of Essential Oils and Antibiotics Against Antibiotic-Resistant Food Borne Disease Bacteria in Burkina Faso - Sodéré P; Somda MK; Zongo L; Mihin HB; Mogmenga I; Akakpo AY; Dicko MH (Infection and Drug Resistance, 2025)
Paul Sodéré,1,2 Marius K Somda,1,2 Luc Zongo,3,4 Henriette B Mihin,1 Iliassou Mogmenga,2,5 Agbémébia Y Akakpo,1 Mamoudou H Dicko2 1Laboratory of Microbiology and Microbial Biotechnology, Department of Biochemistry and Microbiology, University Joseph KI-ZERBO, Ouagadougou, 03 BP: 7021, Burkina Faso; 2Laboratory of Biochemistry Biotechnology Food Technology and Nutrition, Department of Biochemistry Microbiology, University Joseph KI-ZERBO, Ouagadougou, 03 BP: 7021, Burkina Faso; 3Hospital Saint Camille of Ouagadougou (HOSCO), Ouagadougou, 09 BP 444, Burkina Faso; 4Faculty of Health Sciences, University Saint Thomas d’Aquin (USTA), Ouagadougou, 06 BP 10212, Burkina Faso; 5Banfora University Centre, University Nazi Boni, Bobo-Dsso, 01 BP: 1091, Burkina FasoCorrespondence: Paul Sodéré, Laboratory of Microbiology and Microbial Biotechnology, Department of Biochemistry and Microbiology, University Joseph KI-ZERBO, Ouagadougou, 03 BP: 7021, Burkina Faso, Email Soderepaul@yahoo.frBackground: Bacterial resistance to antibiotics is an important developing threat for human health. Therefore, searching for alternatives through the synergistic combination of essential oils with conventional antibiotics is one of the relevant approaches. This study aims to investigate the mechanism of action of essential oils isolated from local common medicinal plants of Burkina Faso (Hyptis suaveolens and Laggera aurita) combined with three antibiotics (ciprofloxacin, amoxicillin + clavulanic acid and colistin) against resistant-bacterial strains (08) involved in toxi–intoxic effects (Staphylococcus aureus ATCC 2523, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 9027, Enterococcus faecalis 0366 V, Salmonella typhi SKN 1152, Bacillus cereus 0998 V, Bacillus subtilis 0486 V, Yersinia enterocolitica 0938 V).Methods: The methodological approach consisted of evaluating the antibacterial activity followed by investigating antibacterial mechanism.Results: The MICs (minimum inhibitory concentration) of Laggera aurita and Hyptis suaveolens ranged from 4.05 mg/mL to 64.92 mg/mL and from 9.57 mg/mL to 38.28 mg/mL, respectively. Checkerboard assays revealed synergistic effects resulting in reductions of 93.69% and 87.73%, respectively, in amoxicillin+ clavulanic acid and colistin MICs. Protein and nucleic acid leakage assays demonstrated that peptidoglycan and cytoplasmic membrane damage induced by the synergistic combination were significantly greater than those in the control. The viable count of bacteria for this combination showed a complete killing profile after 12 hours and further.Conclusion: It appears from this study that the combinations (essential oil-antibiotic) reduced the MICs of the antibiotics and eradicated antibiotic-resistant bacteria completely. This combination could constitute an excellent means against bacterial resistance to antibiotics.Keywords: antibacterial activity, antibiotics, essential oils, Hyptis suaveolens, Laggera aurita, mechanisms